Pengaruh Profesionalitas Guru Terhadap Perkembangan Potensi Belajar Siswa Dalam Mata Pelajaran Akidah Akhlak Di Madrasah Aliyah Al-Ikhlas Ujung - Arifuddin, Arifuddin (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research is the research field. Research methodology is ex-post facto quantitative descriptive-shaped, with the approach of pedagogy, psychology, and sociology. As for the data collection techniques are observation, interview, question form, and documentation. Technique of data analysis used a simple linear regression analysis, namely, using the Test validity and Reliability, Classic Assumption Test i.e. Test Normality Test, Autocorrelation, Multicollinearity, test and test Heteroskedastisitas. Research results in the process of teacher professional learning moral soundness in Madrasah Aliyah Al-Ikhlas Tip belongs either. This is in accordance with the results of the analysis of the answers of respondents obtained average value 60.11%, this category belongs to both. Sedangkang learning potential of students in the learning process of the moral soundness of Madrasah Aliyah at Al-Ikhlas Tip belongs either. This is in accordance with the results of the analysis of the answers of respondents obtained average value of 60.87%, this category belongs to both. On the basis of a simple linear regression test obtained regression coefficient values of significant value and of 0564 0000 stated less than 0.05 confidence level so that the professional teacher variables influence the positive and significantly to student learning potential. It can be inferred that the professionalism of teachers and significant positive effect against a potential learning students at Madrasah Aliyah Al-Ikhlas ends.